2011
DOI: 10.1364/oe.19.017996
|View full text |Cite
|
Sign up to set email alerts
|

Measuring frequency noise and intrinsic linewidth of a room-temperature DFB quantum cascade laser

Abstract: The frequency-noise power spectral density of a room-temperature distributed-feedback quantum cascade laser emitting at λ = 4.36 μm has been measured. An intrinsic linewidth value of 260 Hz is retrieved, in reasonable agreement with theoretical calculations. A noise reduction of about a factor 200 in most of the frequency interval is also found, with respect to a cryogenic laser at the same wavelength. A quantitative treatment shows that it can be explained by a temperature-dependent mechanism governing the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
65
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 21 publications
11
65
1
Order By: Relevance
“…The short non-radiative lifetime that dominates the threshold of the QCL also appears to have the beneficial effect of significantly reducing the spectral width 27,28 . Although distributed-feedback lasers processed from ICL wafers using earlier-generation designs have produced 29 mW or more of singlemode CW output at thermoelectric cooler temperatures 29 , the true spectral linewidth of the distributed-feedback ICLs has not been measured to date, although spectrometer-resolution-limited lines have been observed 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The short non-radiative lifetime that dominates the threshold of the QCL also appears to have the beneficial effect of significantly reducing the spectral width 27,28 . Although distributed-feedback lasers processed from ICL wafers using earlier-generation designs have produced 29 mW or more of singlemode CW output at thermoelectric cooler temperatures 29 , the true spectral linewidth of the distributed-feedback ICLs has not been measured to date, although spectrometer-resolution-limited lines have been observed 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The QCLs frequency noise was measured using a spectroscopic setup as implemented in former studies [7,[10][11][12]. The side of a molecular transition was used as a frequency-to-intensity converter (a so-called frequency Here, a 10-cm-long sealed glass cell filled with 2 mbar of pure N 2 O was used with QCLs emitting in the 7.6-8 μm wavelength range.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the char-acterization and understanding of the origin of frequency noise spectrum of free-running QCLs gained a significant interest in the recent years. A few research groups reported experimental frequency noise spectra for QCLs produced by different manufacturers and operated at temperatures ranging from cryogenic [7,9] up to room temperature [6,10,11]. Significantly different levels of noise have been observed in the considered QCLs, leading to linewidths in the range of sub-100 kHz [6] to many megahertz [7].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 For the most demanding applications in the field of high-resolution spectroscopy, frequency-noise analysis revealed that feedback loop bandwidths of several hundred of kHz are necessary for linewidth narrowing of DFB-QCLs. 7,8 While the picosecond carrier lifetime in QCLs allows a very fast modulation of the intensity above 10 GHz, 9,10 the modulation of the optical frequency-or wavelength-is limited by the thermal dynamics of the device. Indeed, unlike interband semiconductor laser diodes whose wavelength can be modulated at high speed through carrier density modulation, 11,12 the latter has no effect in QCLs because of the symmetric gain curve and associated independence of the refractive index at the gain peak (zero alpha parameter).…”
mentioning
confidence: 99%
“…The conversion factor, or frequency discriminator, is given by the slope of the absorption line. Similar setups were used for frequencynoise characterization of free-running mid-IR 7,8 and THz…”
mentioning
confidence: 99%